Medical aspects of disability for the rehabilitation professional - Moroz, Alex; Flanagan, Steven R.; Zaretsky, Herbert H. (Springer Publishing Company, 2017)
The fifth edition of this landmark volume has been substantially updated and expanded to encompass an abundance of innovative rehabilitation research supported by changing technology and new research methodologies. Written for rehabilitation practitioners, researchers, and students, it distills crucial new information regarding aspects of disability pertaining to medical conditions commonly encountered in rehabilitation settings. The fifth edition addresses new topics at the forefront of medical rehabilitation and disability from clinical, functional, and psychological perspectives, including traumatic brain injury, stroke and spinal cord injury, limb deficiency, organ transplantation, geriatric rehabilitation, and new and technology-based rehabilitation research. The book delivers new findings about social work in physical medicine, complementary and alternative treatments, trends in treatment delivery and payment systems, relevant legislation, and telerehabilitation. New chapter authors?noted authorities in their fields?address rheumatic diseases, stroke, rehabilitation nursing, research directions, and integrative medicine, among other topics. The text continues to be the only guide to medical aspects of disability for nonphysician rehabilitation professionals and other health care providers outside of rehabilitation medicine. It serves as a comprehensive guide on what to expect and how to manage each medical issue, causative agents, classification, pain management, psychological factors, and more.